2021
DOI: 10.1111/cdoe.12670
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of a lay health advisor intervention on immigrant children’s dental caries and maternal preventive behaviour: A randomized controlled trial

Abstract: Objectives An oral health disparity exists between native and immigrant children in Taiwan. This study evaluated the long‐term effectiveness of a lay health advisor (LHA) intervention on immigrant children's dental caries and maternal preventive behaviours. Methods Fifty‐one immigrant mother‐child pairs were randomly assigned to LHA intervention (n = 23) and control (n = 28) groups. Mothers in the LHA group received a four‐chapter one‐on‐one lesson plan, which included dental caries–related knowledge, brushing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The results revealed that the participants' mouth self‐examination after the intervention enhanced their self‐efficacy and reduced barriers to oral cancer screening. Another LHA intervention study 17 conducted in Taiwan reported that at the 8‐month postintervention follow‐up, the use of the LHA strategy among immigrant women improved maternal preventive behaviour, such as assisting their children in toothbrushing. Interventions, such as those that incorporate sending reminders, can improve or maintain participants' adherence to medication, influenza vaccination and mammography screening 38–40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results revealed that the participants' mouth self‐examination after the intervention enhanced their self‐efficacy and reduced barriers to oral cancer screening. Another LHA intervention study 17 conducted in Taiwan reported that at the 8‐month postintervention follow‐up, the use of the LHA strategy among immigrant women improved maternal preventive behaviour, such as assisting their children in toothbrushing. Interventions, such as those that incorporate sending reminders, can improve or maintain participants' adherence to medication, influenza vaccination and mammography screening 38–40 .…”
Section: Discussionmentioning
confidence: 99%
“…13 Another Taiwanese study confirmed a community-level LHA intervention can enhance the level of dental caries-related knowledge and dental caries preventive behaviours of immigrant mothers, leading to lower dental caries among immigrant children over 8 months. 17 Oral health promotion programs for community-dwelling older adults can improve oral health-related quality of life. 18 Early oral health intervention may be a valuable and actionable target for older adults as a means of maintaining their quality of life.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation